In vitro haematological studies of stichopodidae sp and holothuriidae sp - Hadzir, Siti Norhaiza (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
Thrombosis is a pathologic condition that occurs when the body forms arterial or venous blood clots that are excessively large and obstruct blood flow. Aspirin and ticlopidine has been widely used as prophylactic inhibitors for platelet aggregation and anticoagulants such as coumadin (warfarin) and heparin are used as a conventional treatment for thrombosis prevention, it is however, difficult to control them due to many factors that can contribute to coagulation. Further, prolonged usage of aspirin and ticlopidine have been implicated with peptic ulceration and gastrointestinal disturbances; and the use of warfarin and heparin have been shown to cause haemorrhage, necrosis of skin, gastro intestinal disturbances, thrombocytopenia and allergy reactions. Therefore, the search for more effective agents that can secw·e full antithrombotic benefits while minimizing the antihaemostatic outcome should be pursued. This could help to prevent the often lethal consequences of the conditions mentioned above. A part from hastening wound healing, opsonizations of leucocytes to the wound site were observed with I 0% gamat solution in an earlier unpublished observation. (SSJ Mohsin-personal communication). This observation prompted the idea of looking at the effects of sea cucumber extracts (gamat in Malay) on haematological parameters. In this study, the extracts of sea cucumbers (Holothuriidae sp and Stichopodidae sp.), will be investigated as a potential antithrombotic agents An initial study will be undertaken to look for changes in mean platelet volume (MPV) using automated Ceii-Dyn 4000 haematology analyzer. Six different healthy voluntary donors were chosen randomly and used as sample. One (1) ml of blood was placed into seven tubes containing O.Olml of PBS (control) and extracts of two species of sea cucumber at different concentrations were used. In this study the concentration used were at O.lmglml, l.Omglml, and IOmglml Stichopodidae sp.; O.lmg/ml, l.Omg/ml and I Omglml Holothuriidae sp. The effective dose on blood was determined for duration of 2 hours with 30 minutes interval from the time of the extract were added to the blood specimen. RM ANOV A revealed that there were no significant different of mean platelet volume between the seven groups tested. However, for within group analysis (time effect) of the species, only Holothuriidae sp. showed significant different. The results from these experiments will establish the direction of subsequent studies in vivo using laboratory animals. The proposed in vivo studies were to assess the eftect of gamat extracts on platelet functions at various concentrations of Holothuriidae and Stichopodidae species. Test group animals which have been initially induced to have hypercoagulable states will be used to compare with the non-treated and vehical treated groups. Blood viscosity, coagulation parameters, haematological parameters and platelet morphology and platelet function t~sts will be done on the blood samples of treated and control groups of animals. The potential anti-thrombotic properties of different species of gamat can only be elucidated following the extensive in vivo studies as mentioned above.